Single-stage resection and microwave ablation for bilobar colorectal liver metastases. Issue 8 (18th May 2016) - Philips, P; Groeschl, R T; Hanna, E M; Swan, R Z; Turaga, K K; Martinie, J B; Iannitti, D A; Schmidt, C; Gamblin, T C lark; Martin, R C G
Abstract: Background: Patients undergoing liver resection combined with microwave ablation (MWA) for bilobar colorectal metastasis may have similar overall survival to patients who undergo two-stage hepatectomy, but with less morbidity. Methods: This was a multi-institutional evaluation of patients who underwent MWA between 2003 and 2012. Morbidity (90-day) and mortality were compared between patients who had MWA alone and those who underwent combined resection and MWA (CRA). Mortality and overall survival after CRA were compared with published data on two-stage resections. Results: Some 201 patients with bilobar colorectal liver metastasis treated with MWA from four high-volume institutions were evaluated (100 MWA alone, 101 CRA). Patients who had MWA alone were older, but the groups were otherwise well matched demographically. The tumour burden was higher in the CRA group (mean number of lesions 3·9 versus 2·2; P = 0·003). Overall (31·7 versus 15·0 per cent; P = 0·006) and high-grade (13·9 versus 5·0 per cent; P = 0·030) complication rates were higher in the CRA group. Median overall survival was slightly shorter in the CRA group (38·4 versus 42·2 months; P = 0·132) but disease-free survival was similar (10·1 versus 9·3 months; P = 0·525). The morbidity and mortality of CRA compared favourably with rates in the existing literature on two-stage resection, and survival data were similar. Conclusion: Single-stage hepatectomy and MWA resulted in survival similar to that following two-stage hepatectomy, with less overall morbidity. Abstract : Attractive strategy